Pengaruh Yoga Terhadap Nyeri Punggung Bawah Pada Ibu Hamil Trimester III di Puskesmas Kalikajar I Kabupaten Wonosobo - Resmi, Dewi Candra; Saputro, Soeharyo Hadi; Runjati, Runjati (Fakultas Ilmu Kesehatan (FIKES) Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo, 2017)
Pregnancy is a physiological thing that occurs in women. Every pregnancy will change both the physical and psychological changes in the mother. In fact, not infrequently these changes will cause discomfort felt by the mother. Lower back pain is one of the discomforts. So it is necessary to do management to overcome one of them is by doing yoga. Yoga is a practical effort in harmonizing body, mind, and spirit, in which the benefits of yoga form a solid posture, and fostering a flexible and strong muscle, purifying the central nerves found in the spine (Devi M, 2014). Objective: to determine the effect of yoga on lower back pain of pregnant women. Quasy eksperimental method with pre and post-equivalence research design is used in this research, 14 respondents become a samples by used VAS (Visual Analog Scale) measuring instrument. Result of research that difference of before and after yoga is 1,43 with result of T test test show value p = 0,000 (<0,05). This suggests that there is a significant effect of yoga on decreasing the intensity of lower back pain of pregnant women. Keywords : Pregnancy, Yoga, lower back pain.